Hydrothermal reduction of CO2 captured by aqueous amine solutions into formate: Comparison between in situ generated H2 and gaseous H2 as reductant and evaluation of amine stability - Laura Quintana-Gómez; Luana Cristina Dos Santos; Fernando Cossio-Cid; Víctor Ciordia-Asenjo; Miguel Almarza; Alberto Goikoechea; Sergio Ferrero; Celedonio M․ Álvarez; José J․ Segovia; Ángel Martín; M․Dolores Bermejo (Carbon Capture Science & Technology)
ABSTRACT: By CO2 Capture and Utilization technologies (CCU), organic compounds can be produced industrially in a sustainable manner, generating an economic benefit that offsets the cost of CO2 capture. In this context, the use of CO2 chemisorbed by amines to generate chemicals is an attractive alternative, given that large-scale facilities using absorption to capture CO2 are already operational. The aim of this work is to convert CO2 captured in aqueous amines, specifically 3-amino-1-propanol (AP) and 2-amino-2-methyl-1-propanol (AMP), to produce formate, using either Zn, Al or gaseous H2 as reductants and Pd/C as catalyst. The highest yield of formate (68 %) was achieved with AP (125 °C, 75 bar, 120 min) using gaseous hydrogen as reductant. Using metals as reductants, reaction yields were lower, with a 12 % yield at 200 °C as the best result. After reduction, NMR analyses show that the amines did not suffer degradation, raising the possibility of reusing them for CO2 capture in a continuous process. These results indicate that CO2-loaded amines reduction is a promising CCU technology that can be integrated with the current technologies for gas treatment.